Gerard Grisey and the Foliation of Time. - Castanet, P.A.; Fineberg, Joshua (Contemporary Music Review, 2000)
Describes the music of composer Gerard Grisey. Influence of nature on the works of composers; Musical instruments and techniques used by Grisey in his music from 1970 to 1980; Musical inspirations of Grisey.